Formative Assessment - Construction for Collaborative Learning in Students of Art and Design - Hermoza Samanez, Luz Marina (2015)
The objective of the experience that we are presenting is to point out some valuable accomplishments of students’ learning from the Geometric Design 1 and 2, DG courses in the Pontificia Universidad Católica del Perú, PUCP’s, Art Faculty, which are built when learning evaluations take place, as well as how the approach of the formative evaluation supports the construction of an art student who is independent and self-directed, able to be conscious of his own progress, able to be self-critical of his/her artistic production, basing their self-evaluation on objective criteria that they themselves will discover and create. In addition, the formative approach of the evaluation promotes the formation of a strong character for critical evaluation, understood here as a specific evaluation strategy of art and design.Also we will reflect on the application of evaluation strategies aimed towards being collaborative; to give meaning to the method and to the intended contents of the learning while the student is acquiring procedure tools for the development of drawing techniques and for their own self-expression.This important learning is aimed at the autonomy of the student, because simultaneously to the conceptual area, diverse methodologies will be put in practice and students will experience strategies of collaborative learning andindividual aimed to «learning to learn» and «learning to be».